2018
DOI: 10.1002/ecy.2143
|View full text |Cite
|
Sign up to set email alerts
|

Litter removal in a tropical rain forest reduces fine root biomass and production but litter addition has few effects

Abstract: Many old-growth lowland tropical rain forests are potentially nutrient limited, and it has long been thought that many such forests maintain growth by recycling nutrients from decomposing litter. We investigated this by continuously removing (for 10 yr) freshly fallen litter from five (45 m × 45 m) plots, adding it to five other plots, there were five controls. From monthly measures over 1 yr we show that litter removal caused lower: fine root (≤2 mm diameter) standing mass, fine root standing length, fine roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…On the other hand, in spite of the light lower concentration in extractable P in mineral soil found in the mixed-species stand, a previous study (Koutika et al 2016) revealed a higher foliar P concentration in these stands. The results of the present study are in agreement with previous studies, showing that forest floor might be playing an important role in the P dynamics in forest ecosystems (Lang et al 2017;Rodtassana and Tanner 2018). On one hand, the P input through litter decomposition and microbial activity ensures the supply of P to the plant.…”
Section: P In Mineral Soilssupporting
confidence: 93%
“…On the other hand, in spite of the light lower concentration in extractable P in mineral soil found in the mixed-species stand, a previous study (Koutika et al 2016) revealed a higher foliar P concentration in these stands. The results of the present study are in agreement with previous studies, showing that forest floor might be playing an important role in the P dynamics in forest ecosystems (Lang et al 2017;Rodtassana and Tanner 2018). On one hand, the P input through litter decomposition and microbial activity ensures the supply of P to the plant.…”
Section: P In Mineral Soilssupporting
confidence: 93%
“…Fine-root dynamics was influenced by rainfall patterns with greater productivity and mortality in the rainy season, mainly in the surface soil, which is consistent with patterns observed in other tropical regions (Cavelier et al, 1999;Green, Dawson, Proctor, Duff, & Elston, 2005;Rodtassana & Tanner, 2018;Yavitt & Wright, 2001) and in the Amazonia basin (Girardin et al, 2016;Metcalfe et al, 2008). The higher root growth with precipitation can be related to both physical and chemical properties of the soil.…”
Section: Seasonal Variation In Root Dynamicssupporting
confidence: 85%
“…We used the ingrowth core method to measure fine root growth and to obtain an estimate of annual fine root production (Neill, 1992; Hertel et␣al ., 2013; Rodtassana & Tanner, 2018; Li et␣al ., 2020). Each ingrowth core was 2.4 cm in diameter and 10 cm tall and consisted of soil contained in a high‐density polyethylene net cylinder with a 2 mm mesh.…”
Section: Methodsmentioning
confidence: 99%